Valoración de proyectos de empresas con teoría de opciones reales – caso Enersur S.A. - González Vásquez, Joe Alexis (2016)
This research aims to be useful to the academic community, the company in the study and wider society through knowledge and the implementation of a pricing model projects of companies with real options theory (TOR), which submit the proposals and assessment of real applications of an investment project of hydroelectric generation. This assessment is carried out a project of a hydroelectric plant using the real options theory and other traditional methods of valuation, it is concluded that the techniques of influencing Adjusted Present Value (APV) and Internal Rate of Return (IRR), do not take into account the flexibility that often has an investment and course changes and decisions that can be taken during the life of an investment project. It has developed a descriptive study which defines the concept of valuation extensively, studying classical methods, discounting cash flows, value creation, valuation using real options theory and method of valuation the residual result. Finally it determined the impact of the valuation of company projects using real options theory indicators of profitability in the company EnerSur S.A., showing a significant improvement.